2022
DOI: 10.1186/s12871-022-01770-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of recovery in patients administered remimazolam versus those administered an inhalant agent for the maintenance of general anesthesia: a randomized control trial

Abstract: Background Remimazolam is a novel intravenous benzodiazepine that is appropriate for the maintenance of anesthesia. Quality of recovery is an important component of health care quality, but there is no published randomized control trial focused on the quality of recovery in patients undergoing total intravenous anesthesia with remimazolam. Methods This parallel-group, single-blind randomized control trial at a tertiary care medical center in South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Hari et al [ 23 ] found that the incidence of early PONV was lower after the administration of remimazolam than after the administration of desflurane in patients undergoing laparoscopic gynecologic surgery. Song et al [ 24 ] also demonstrated that the incidence of early PONV was lower with remimazolam than with desflurane in patients undergoing laparoscopic cholecystectomy or robot-assisted gynecological surgery. These findings, although limited, indicate that PONV is less likely to occur with remimazolam than with inhaled anesthetic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Hari et al [ 23 ] found that the incidence of early PONV was lower after the administration of remimazolam than after the administration of desflurane in patients undergoing laparoscopic gynecologic surgery. Song et al [ 24 ] also demonstrated that the incidence of early PONV was lower with remimazolam than with desflurane in patients undergoing laparoscopic cholecystectomy or robot-assisted gynecological surgery. These findings, although limited, indicate that PONV is less likely to occur with remimazolam than with inhaled anesthetic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative nausea and vomiting can be minimized by maintaining anesthesia with remimazolam [14]. The patient did not complain of nausea and vomiting during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…The time to the loss of consciousness following the administration of remimazolam was similar to that of conventional hypnotic agents. The time to emergence of consciousness after cessation of remimazolam administration is usually 10 to 20 minutes [14]. Flumazenil can readily reverse the effect of benzodiazepine when emergence is prolonged or intraoperative awakening of a patient is required.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, prompt and reliable awakening is considered very important for early detection of cranial nerve complications. In addition, remimazolam is reported to be advantageous for postoperative recovery 13) . Clear arousal may also reduce the workload of the physician in charge by providing an opportunity to rule out cranial nerve complications immediately after surgery, which may simplify postoperative patient explanation and patient management.…”
Section: Discussionmentioning
confidence: 99%